The Effectiveness of Digital Literacy to Improve Students’ Reading Comprehension and Critical Thinking - Aisyah, Noor; Khadijah, Sitti; Azmi, Aulia (Journal of Language Intelligence and Culture, 2025)
This study examines whether integrating digital literacy–based activities into English for Academic Purposes (EAP) instruction enhances undergraduate students’ academic reading skills and critical thinking. Addressing a gap in the literature where academic reading and critical thinking are often treated as separate outcomes and digital literacy is frequently reduced to tool use, this study conceptualizes digital literacy as a pedagogical framework that supports higher-order engagement with academic texts. Eight sessions of digitally enhanced EAP instruction were implemented in an experimental class (n = 44), focusing on students’ abilities to critically access, evaluate, and construct meaning from academic readings, while the other class (n = 45) received conventional EAP instruction. The results revealed that the experimental group achieved significantly greater gains than the control group in both academic reading (U = 596.50, p = 0.001) and critical thinking (U = 253.00, p < 0.001). These findings suggest that digital literacy functions as a mediating pedagogical approach that deepens students’ engagement with academic texts and fosters higher-order reasoning. Conceptually, the study extends EAP instructional models by demonstrating that academic reading and critical thinking can be developed simultaneously through integrated digital literacy practices. The study recommends that EAP instructors systematically embed digital literacy–oriented activities to strengthen students’ academic literacy.